2015
DOI: 10.1021/acs.macromol.5b01544
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Aqueous Methylcellulose Solutions

Abstract: The weight-average molecular weight M w , z-average radius of gyration R g , and second virial coefficient A 2 have been determined between 15 and 52 °C for dilute aqueous solutions of methylcellulose (MC) with three different molecular weights and constant degree of substitution (DS) of 1.8 using static light scattering. These measurements, conducted within 1 h of heating the homogeneous solutions from 5 °C, reveal that the theta temperature for MC in water is T θ = 48 ± 2 °C, with A 2 < 0 for T > T θ , indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 75 publications
(151 reference statements)
5
81
0
Order By: Relevance
“…The last step in the modeling is describing the rheology. As already discussed by Arvidson et al, the elasticity of the MC fibrillar network at high temperature should be similar to that of the actin network or any other network of semi‐flexible fibers. The elasticity of semi‐flexible fibrillar network is often described by the model of MacKintosh et al, resulting in a strong dependence of the shear storage modulus, G’ , on the polymer concentration, c , as G’ ∼ c 2.5 This result is indeed consistent with experiments for the case of gelatin networks, as demonstrated by Joly‐Duhamel et al We use the same modeling approach to compute the dependence of G’ ( T ) for various concentrations of aqueous MC, while estimating the crosslink density as function of temperature from thermodynamic theory.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…The last step in the modeling is describing the rheology. As already discussed by Arvidson et al, the elasticity of the MC fibrillar network at high temperature should be similar to that of the actin network or any other network of semi‐flexible fibers. The elasticity of semi‐flexible fibrillar network is often described by the model of MacKintosh et al, resulting in a strong dependence of the shear storage modulus, G’ , on the polymer concentration, c , as G’ ∼ c 2.5 This result is indeed consistent with experiments for the case of gelatin networks, as demonstrated by Joly‐Duhamel et al We use the same modeling approach to compute the dependence of G’ ( T ) for various concentrations of aqueous MC, while estimating the crosslink density as function of temperature from thermodynamic theory.…”
Section: Introductionmentioning
confidence: 63%
“…Here, ϕ is the methylcellulose volume fraction in water, and α ≈ 0.4 is the volume fraction of polymer in the tube (we assume that it is the same as in experiments of Arvidson et al). The free energy density of the ensemble of rings/tubes in water can be written as follows, fknormalBT=true{ρ1lntrue(ρ1etrue)+ρ2lntrue(2ρ2etrue)+ρ3lntrue(3ρ3etrue)true}+ε1ρ1+ε2ρ2+ε3ρ3+Ktrue(ρ1+2ρ2+3ρ3νtrue) …”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the crowding agent, methylcellulose, we employed. Methylcellulose is a large, viscous polymer that can form bundles on its own at high concentrations 45 . Here, we use it at 0.3% in the chamber, which should be in the isotropic network phase 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Studying the self-assembly of model diblock copolymers having unsubstituted glucose/cellobiose as hydrophilic heads and regioselectively methylated or permethylated glucose units as hydrophobic tails with a total DP of ≤ 28, Nakagawa et al [5] showed the necessity of a sequence of at least 10 permethylated glucosyl units for gelation of methylcellulose to happen. Fibril formation prior to gelation was also observed and further studied using a systematic coarsegrained model [6][7][8][9][10][11][12][13][14]. Taking into account the role of highly methylated glucose units in thermogelation of methylcellulose, Adden et al [15] suggested the cationic ring-opening polymerization of differently substituted cyclodextrins as a potential method for synthesis of glucan ether block copolymers having blocks of permethylated glucose units.…”
Section: Introductionmentioning
confidence: 99%